Evaluation of a teacher training program to enhance executive functions in preschool children - Walk, Laura; Evers, Wiebke; Quante, Sonja; Hille, Katrin (PLOS ONE, 2018)
Background Executive functions (EFs) play a critical role in cognitive and social development. During preschool years, children show not only rapid improvement in their EFs, but also appear sensitive to developmentally appropriate interventions. Aim EMIL is a training program for German preschool teachers that was developed and implemented to improve the EFs of preschoolers. The aim of the present study was to evaluate its effects on the EFs of children between three and six years old. Method The teacher training (eight sessions, 28.5 hours) was implemented in four preschools. The EFs of children of the intervention group (n = 72, 32 girls, Mage = 48 months) and the control group of four other matched preschools (n = 61, 27 girls, Mage = 48 months) were tested before, during, and after the intervention using different measures assessing working memory, inhibitory control, and cognitive flexibility. Results The intervention group showed significant gains on three out of seven EF tests (behavioral inhibition, visual-spatial working memory, and combined EFs) compared to the control group. Post hoc analyses for children with low initial EFs scores revealed that participation in the intervention led to significant gains in inhibitory control, visual-spatial working memory, and phonological working memory as well as a marginally significant difference for combined EFs. However, effect sizes were rather small. Conclusion The results suggest that teacher training can lead to significant improvements in preschooler’s EFs. Although preliminary, the results could contribute to the discussion on how teacher training can facilitate the improvement of EFs in preschool children.
Gesehen am 25.04.2019